ImageJ SurfCut: a user-friendly pipeline for high-throughput extraction of cell contours from 3D image stacks - Erguvan, Özer; Louveaux, Marion (BMC biology, 2019)
Many methods have been developed to quantify cell shape in 2D in tissues. For instance, the analysis of epithelial cells in Drosophila embryogenesis or jigsaw puzzle-shaped pavement cells in plant epidermis has led to the development of numerous quantification methods that are applied to 2D images. However, proper extraction of 2D cell contours from 3D confocal stacks for such analysis can be problematic.